Adaptive Behavior and Quality of Life of adults with intellectual disabilities: Psychomotor Therapy as support - Mariana Freitas; Sofia Santos (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2018)
Background: The increased scientific recognition of Quality of Life (QOL) and adaptive behavior constructs implies changes in practice aligned with the supports person-centred provision. The alignment between these constructs is been recently proven at theoretical level but it still lacks of practical evidences-based.  Purpose: This article' goal is to analyses the practical relations among measures of all constructs, through the examination how psychomotor therapy, as one of the supports provided, to adults with Intellectual Disability (ID), can contribute for a better adaptive behavior performance and for a life with more quality. The three Portuguese versions of Adaptive Behavior, Supports Intensity and Personal Outcomes Scales were applied to 11 adults with IDD, between 24 and 45 years (32.64±6.92), five females and six males, institutionalized. All participants were assessed in three different moments: before and after intervention, and one month later for the retention assessment. Baseline results allowed the planning and implementation of a 6-month psychomotor program, with weekly sessions of 50 minutes.  Results: Results showed better adaptive level and positive personal outcomes, as well a reduction of supports needs. Psychomotor therapy may have positive effects on independent functioning level of adults with IDD. Further, results pointed out a positive and moderate correlation between QOL and adaptive behavior but negative and moderate with supports needs.